Perceptions of a Group of Surgical and Non-Surgical Residents at a Hispanic Academic Medical Center of the Impact of the Night-Float System - Colón-de Martí, Luz N.; Martínez, Angeles; Gómez, Yolanda; Rivera-Colón, Irma (Puerto Rico Health Sciences Journal, 2014)
Objective: In 2003 the ACG ME implemented mandatory work-hour limitations to address concerns about the negative effects of sleep deprivation on resident wellbeing and patient safety. The night-float system (NFS) is an attempt to promote a balance between optimal patient care and well-rested residents. The aim of this study was to assess and compare the perceptions of surgical and non-surgical residents with regard to the impact of the NFS on their education, their well-being, and aspects related to patient care. Methods: After the approval from the Institutional Review Board was received, residents (241) from the UPR School of Medicine residency programs were invited to participate. Those residents who chose to take part in the study (149) completed a questionnaire with demographic questions and items related to individual perceptions of the impact of the NFS. The questionnaires, collected from April 2010 through September 2010, were categorized as having come from a surgical or nonsurgical resident. Data were analyzed. Results: The response rate was almost sixty-two percent (61.8%).Of the residents who answered the questionnaire, 63% were in non-surgical programs, 51% were female, and 58% were single. Seventy-three percent of the residents had participated in an NFS. Sixty-two percent disagreed that their participation in the NFS improved their sense of well-being. Seventy-six percent agreed that their participation improved the continuity of care for the emergency room patients under their responsibility. A higher percentage of the non-surgical residents than surgical residents agreed that during their participation in the NFS, their relationships with their spouses/significant others and children (if applicable), sleep patterns and hours, peer support, and work/ rest balance were impacted negatively. Conclusion: This group of residents presented significant differences between the non-surgical and the surgical groups in areas related to well-being, which the majority agreed was negatively impacted during their participation in the NFS.